EFL students' use of grammatical information in five leading British learners' dictionaries - Alenka Vrbinc; Marjeta Vrbinc (Linguistica, 2007)
Grammar is one of the elements of lexicographic description. In order to find out whether dictionary users use their dictionaries to retrieve grammatical information, we carried out a research-based study investigating their skills. This article presents and discusses the results of a study into the use by EFL students of grammatical information included in five leading British learners' dictionaries. The ability of students to use dictionary entries was tested by means of 33 sentences. Some of the sentences were grammatically correct; others contained a grammatical mistake. The students had to detect mistakes with the help of enclosed dictionary entries. The aim of the study was to find out whether there were any great differences among the dictionaries used and how successful the test subjects were in finding and using grammatical information.